4th Pediatric Allergy and Asthma Meeting (PAAM). Issue 1 (November 2016) - Yavuz, S.; Koc, Ozan; Gungor, Ali; Gok, Faysal; Hawley, Jessica; O'Brien, Christopher; Thomas, Matthew; Brodlie, Malcolm; Michaelis, Louise; Mota, Inês; Gaspar, Ângela; Piedade, Susana; et al.
Table of contents WORKSHOP 4: Challenging clinical scenarios (CS01–CS06) CS01 Bullous lesions in two children: solitary mastocytoma S. Tolga Yavuz, Ozan Koc, Ali Gungor, Faysal Gok CS02 Multi-System Allergy (MSA) of cystic fibrosis: our institutional experience Jessica Hawley, Christopher O'Brien, Matthew Thomas, Malcolm Brodlie, Louise Michaelis CS03 Cold urticaria in pediatric age: an invisible cause for severe reactions Inês Mota, Ângela Gaspar, Susana Piedade, Graça Sampaio, José Geraldo Dias, Miguel Paiva, Mário Morais-Almeida CS04 Angioedema with C1 inhibitor deficiency in a girl: a challenge diagnosis Cristina Madureira, Tânia Lopes, Susana Lopes, Filipa Almeida, Alexandra Sequeira, Fernanda Carvalho, José Oliveira CS05 A child with unusual multiple organ allergy disease: what is the primer? Fabienne Gay-Crosier CS06 A case of uncontrolled asthma in a 6-year-old patient Ioana-Valentina Nenciu, Andreia Florina Nita, Alexandru Ulmeanu, Dumitru Oraseanu, Carmen Zapucioiu ORAL ABSTRACT SESSION 1: Food allergy (OP01–OP06) OP01 Food protein-induced enterocolitis syndrome: oral food challenge outcomes for tolerance evaluation in a Pediatric Hospital Adrianna Machinena, Olga Domínguez Sánchez, Montserrat Alvaro Lozano, Rosa Jimenez Feijoo, Jaime Lozano Blasco, Mònica Piquer Gibert, Mª Teresa Giner Muñoz, Marcia Dias da Costa, Ana Maria Plaza Martín OP02 Characteristics of infants with food protein-induced enterocolitis syndrome and allergic proctocolitis Ebru Arik Yilmaz, Özlem Cavkaytar, Betul Buyuktiryaki, Ozge Soyer, Cansin Sackesen OP03 The clinical and immunological outcomes after consumption of baked egg by 1–5 year old egg allergic children: results of a randomised controlled trial MerrynNetting, Adaweyah El-Merhibi, Michael Gold, PatrickQuinn, IrmeliPenttila, Maria Makrides OP04 Oral immunotherapy for treatment of egg allergy using low allergenic, hydrolysed egg Stavroula Giavi, Antonella Muraro, Roger Lauener, Annick Mercenier, Eugen Bersuch, Isabella M. Montagner, Maria Passioti, Nicolò Celegato, Selina Summermatter, Sophie Nutten, Tristan Bourdeau, Yvonne M. Vissers, Nikolaos G. Papadopoulos OP05 Chemical modification of a peanut extract results in an increased safety profile while maintaining efficacy Hanneke van der Kleij, Hans Warmenhoven, Ronald van Ree, Raymond Pieters, Dirk Jan Opstelten, Hans van Schijndel, Joost Smit OP06 Administration of the yellow fever vaccine in egg allergic children Roisin Fitzsimons, Victoria Timms, George Du Toit ORAL ABSTRACT SESSION 2: Asthma (OP07–OP12) OP07 Previous exacerbation is the most important risk factor for future exacerbations in school-age children with asthma S. Tolga Yavuz, Guven Kaya, Mustafa Gulec, Mehmet Saldir, Osman Sener, Faysal Gok OP08 Comparative study of degree of severity and laboratory changes between asthmatic children using different acupuncture modalities Nagwa Hassan, Hala Shaaban, Hazem El-Hariri, Ahmed Kamel Inas E. Mahfouz OP09 The concentration of exhaled carbon monoxide in asthmatic children with different controlled stadium Papp Gabor, Biro Gabor, Kovacs Csaba OP10 Effect of vitamin D3 supplementation during pregnancy on risk of persistent wheeze in the offspring: a randomised clinical trial Bo Chawes, Klaus Bønnelykke, Jakob Stokholm, Lene Heickendorff, Susanne Brix, Morten Rasmussen, Hans Bisgaard OP11 Lung function development in childhood Henrik Wegener Hallas, Bo Chawes, Lambang Arianto, Hans Bisgaard OP12 Is the effect of maternal and paternal asthma different in female and male children before puberty? Maike Pincus, Thomas Keil, Andreas Reich, Ulrich Wahn, Susanne Lau, Linus Grabenhenrich ORAL ABSTRACT SESSION 3: Epidemiology—genetics (OP13–OP18) OP13 Lifestyle is associated with incidence and category of allergen sensitisation: the ALADDIN birth cohort Sara Fagerstedt, Helena Marell Hesla, Emelie Johansson, Helen Rosenlund, Axel Mie, Annika Scheynius, Johan Alm OP15 Maternal filaggrin mutations increase the risk of atopic dermatitis in children: an effect independent of mutation inheritance Jorge Esparza-Gordillo, Anja Matanovic, Ingo Marenholz, Anja Bauerfeind, Klaus Rohde, Katja Nemat, Min-Ae Lee-Kirsch, Magnus Nordenskjöld, Marten C. G. Winge, Thomas Keil, Renate Krüger, Susanne Lau, Kirsten Beyer, Birgit Kalb, Bodo Niggemann, Norbert Hübner, Heather J. Cordell, Maria Bradley, Young-Ae Lee OP16 Allergic multimorbidity of asthma, rhinitis and eczema in the first 2 decades of the German MAS birth cohort Thomas Keil, Hannah Gough, Linus Grabenhenrich, Dirk Schramm, Andreas Reich, John Beschorner, Antje Schuster, Carl-Peter Bauer, Johannes Forster, Fred Zepp, Young-Ae Lee, Renate Bergmann, Karl Bergmann, Ulrich Wahn, Susanne Lau OP17 Childhood anaphylaxis: a growing concern Filipe Benito Garcia, Inês Mota, Susana Piedade, Ângela Gaspar, Natacha Santos, Helena Pité, Mário Morais-Almeida OP18 Indoor exposure to molds and dampness in infancy and its association to persistent atopic dermatitis in school age. Results from the Greek ISAAC II study Athina Papadopoulou, Despina Mermiri, Elpida Xatziagorou, Ioannis Tsanakas, Stavroula Lampidi, Kostas Priftis ORAL ABSTRACT SESSION 4: Pediatric rhinitis—immunotherapy (OP19–OP24) OP19 Associations between residential greenness and childhood allergic rhinitis and aeroallergen sensitisation in seven birth cohorts Elaine Fuertes, Iana Markevych, Gayan Bowatte, Olena Gruzieva, Ulrike Gehring, Allan Becker, Dietrich Berdel, Michael Brauer, Chris Carlsten, Barbara Hoffmann, Anita Kozyrskyj, Caroline Lodge, Göran Pershagen, Alet Wijga, Heinrich Joachim OP20 Full symptom control in pediatric patients with allergic rhinitis and asthma: results of a 2-year sublingual allergen immunotherapy study Zorica Zivkovic, Ivana Djuric-Filipovic, Jasmina Jocić-Stevanovic, Snežana Zivanovic OP21 Nasal epithelium of different ages of atopic subjects present increased levels of oxidative stress and increased cell cytotoxicity upon rhinovirus infection Styliani Taka, Dimitra Kokkinou, Aliki Papakonstantinou, Panagiota Stefanopoulou, Anastasia Georgountzou, Paraskevi Maggina, Sofia Stamataki, Vassiliki Papaevanggelou, Evangelos Andreakos, Nikolaos G. Papadopoulos OP22 Cluster subcutaneous immunotherapy schedule: tolerability profile in children Monica Piquer Gibert, Montserrat Alvaro Lozano, Jaime Lozano Blasco, Olga Domínguez Sánchez, Rosa Jiménez Feijoo, Marcia Dias da Costa, Mª Teresa Giner Muñoz, Adriana Machinena Spera, Ana Maria Plaza Martín OP23 Rhinitis as a risk factor for asthma severity in 11-year old children: population-based cohort study Matea Deliu, Danielle Belgrave, Angela Simpson, Adnan Custovic OP24 The Global Lung Function Initiative equations in airway obstruction evaluation of asthmatic children João Gaspar Marques, Pedro Carreiro-Martins, Joana Belo, Sara Serranho, Isabel Peralta, Nuno Neuparth, Paula Leiria-Pinto POSTER DISCUSSION SESSION 1: Food allergy (PD01–PD05) PD01 Allergen-specific humoral and cellular responses in children who fail egg oral immunotherapy due to allergic reactions Marta Vazquez-Ortiz, Mariona Pascal, Ana Maria Plaza, Manel Juan PD02 FoxP3 epigenetic features in children with cow milk allergy Lorella Paparo, Rita Nocerino, Rosita Aitoro, Ilaria Langella, Antonio Amoroso, Alessia Amoroso, Carmen Di Scala, Roberto Berni Canani PD04 Combined milk and egg allergy in early childhood: let them eat cake? Santanu Maity, Giuseppina Rotiroti, Minal Gandhi PD05 Introduction of complementary foods in relation to allergy and gut microbiota in farm and non-farm children Karin Jonsson, Annika Ljung, Bill Hesselmar, Ingegerd Adlerbert, Hilde Brekke, Susanne Johansen, Agnes Wold, Ann-Sofie Sandberg POSTER DISCUSSION SESSION 2: Asthma and wheeze (PD06–PD16) PD06 The association between asthma and exhaled nitric oxide is influenced by genetics and sensitisation Björn Nordlund, Cecilia Lundholm, Villhelmina Ullemar, Marianne van Hage, Anne Örtqvist, Catarina Almqvist PD09 Prevalence patterns of infant wheeze across Europe Anna Selby, Kate Grimshaw, Thomas Keil, Linus Grabenhenrich, Michael Clausen, Ruta Dubakiene, Alessandro Fiocchi, Marek Kowalski, Nikos Papadopoulos, Marta Reche, Sigurveig Sigurdardottir, Aline Sprikkleman, Paraskevi Xepapadaki, Clare Mills, Kirsten Beyer, Graham Roberts PD10 Epidemiologic changes in recurrent wheezing infants Herberto Jose Chong Neto, Gustavo Falbo Wandalsen, Ana Carolina Dela Bianca, Carolina Aranda, Nelson Augusto Rosário, Dirceu Solé, Javier Mallol, Luis García Marcos PD13 A single nucleotide polymorphism in the GLCCI1 gene is associated with response to asthma treatment in children IvanaBanic, Matija Rijavec, Davor Plavec, Peter Korosec, Mirjana Turkalj PD14 Pollen induced asthma: Could small molecules in pollen exacerbate the protein-mediated allergic response? Alen Bozicevic, Maria De Mieri, Matthias Hamburger PD15 A qualitative study to understand how we can empower teenagers to better self-manage their asthma Simone Holley, Ruth Morris, Frances Mitchell, Rebecca Knibb, Susan Latter, Christina Liossi, Graham Roberts PD16 Polymorphism of endothelial nitric oxide synthase (eNOS) gene among Egyptian children with bronchial asthma Mostafa M. M. Hassan POSTER DISCUSSION SESSION 3: Mechanisms—Epidemiology (PD17–PD21) PD17 Pregnancy outcomes in relation to development of allergy in a Swedish birth cohort Malin Barman, Anna Sandin, Agnes Wold, Ann-Sofie Sandberg PD18 Evolution of the IgE response to house dust mite molecules in childhood Daniela Posa, Serena Perna, Carl-Peter Bauer, Ute Hoffmann, Johannes Forster, Fred Zepp, Antje Schuster, Ulrich Wahn, Thomas Keil, Susanne Lau, Kuan-Wei Chen, Yvonne Resch, Susanne Vrtala, Rudolf Valenta, Paolo Maria Matricardi PD19 Antibody recognition of nsLTP-molecules as antigens but not as allergens in the German-MAS birth cohort Olympia Tsilochristou, Alexander Rohrbach, Antonio Cappella, Stephanie Hofmaier, Laura Hatzler, Carl-Peter Bauer, Ute Hoffmann, Johannes Forster, Fred Zepp, Antje Schuster, RaffaeleD'Amelio, Ulrich Wahn, Thomas Keil, Susanne Lau, Paolo Maria Matricardi PD20 Early life colonization with Lactobacilli and Staphylococcus aureus oppositely associates with the maturation and activation of FOXP3+ CD4 T-cells Sophia Björkander, Maria A. Johansson, Gintare Lasaviciute, Eva Sverremark-Ekström PD21 Genome-wide meta-analysis identifies 7 susceptibility loci involved in the atopic march Ingo Marenholz, Jorge Esparza-Gordillo, Franz Rüschendorf, Anja Bauerfeind, David P. Strachan, Ben D. Spycher, Hansjörg Baurecht, Patricia Margaritte-Jeannin, Annika Sääf, Marjan Kerkhof, Markus Ege, Svetlana Baltic, Melanie C Matheson, Jin Li, Sven Michel, Wei Q. Ang, Wendy McArdle, Andreas Arnold, Georg Homuth, Florence Demenais, Emmanuelle Bouzigon, Cilla Söderhäll, Göran Pershagen, Johan C. de Jongste, Dirkje S Postma, Charlotte Braun-Fahrländer, Elisabeth Horak, Ludmila M. Ogorodova, Valery P. Puzyrev, Elena Yu Bragina, Thomas J Hudson, Charles Morin, David L Duffy, Guy B Marks, Colin F Robertson, Grant W Montgomery, Bill Musk, Philip J Thompson, Nicholas G. Martin, Alan James, Patrick Sleiman, Elina Toskala, Elke Rodriguez, Regina Fölster-Holst, Andre Franke, Wolfgang Lieb, Christian Gieger, Andrea Heinzmann, Ernst Rietschel, Thomas Keil, Sven Cichon, Markus M Nöthen, Craig E Pennell, Peter D Sly, Carsten O Schmidt, Anja Matanovic, Valentin Schneider, Matthias Heinig, Norbert Hübner, Patrick G. Holt, Susanne Lau, Michael Kabesch, Stefan Weidinger, Hakon Hakonarson, Manuel AR Ferreira, Catherine Laprise, Maxim B. Freidin, Jon Genuneit, Gerard H Koppelman, Erik Melén, Marie-Hélène Dizier, A. John Henderson, Young Ae Lee POSTER DISCUSSION SESSION 4: Food allergy—Anaphylaxis (PD22–PD26) PD22 Atopy patch test in food protein induced enterocolitis caused by solid food Purificacion González-Delgado, Esther Caparrós, Fernando Clemente, Begoña Cueva, Victoria M. Moreno, Jose Luis Carretero, Javier Fernández PD23 Watermelon allergy: a novel presentation Kate Swan, George Du Toit PD24 A pilot study evaluating the usefulness of a guideline template for managing milk allergy in primary care Mudiyur Gopi, Tim Smith, Edara Ramesh, Arun Sadasivam PD26 Efficacy and safety of cow's milk oral immunotherapy protocol Inês Mota, Filipe Benito Garcia, Susana Piedade, Angela Gaspar, Graça Sampaio, Cristina Arêde, Luís Miguel Borrego, Graça Pires, Cristina Santa-Marta, Mário Morais-Almeida POSTER DISCUSSION SESSION 5: Prevention and treatment—Allergy (PD27–PD36) PD27 Allergy-protection by the lactic acid bacterium Lactococcus lactis G121: mode-of-action as revealed in a murine model of experimental allergy Stephanie Brand, Karina Stein, Holger Heine, Marion Kauth PD29 The relationship between quality of life and morning salivary cortisol after acute bronchiolitis in infancy Leif Bjarte Rolfsjord, Egil Bakkeheim, Johan Alm, Håvard Ove Skjerven, Kai-Håkon Carlsen, Jon Olav Hunderi, Teresa Løvold Berents, Petter Mowinckel, Karin C. Lødrup Carlsen PD30 Randomised trial of the efficacy of MP29-02* compared with fluticasone propionate nasal spray in children aged ≥6 years to <12 years with allergic rhinitis Ulrich Wahn, Ullrich Munzel, William Berger PD31 10 mg of oral bilastine in 2 to 11 years old children has similar exposure to the adult therapeutic dose (20 mg) Ulrich Wahn, Román Valiente, Valvanera Vozmediano, John C. Lukas, Mónica Rodríguez PD33 Daily symptoms, nocturnal symptoms, activity limitations and reliever therapies during the three steps of IOEASMA programme: a comparison Sebastiano Guarnaccia, Luigi Vitale, Ada Pluda, Emanuele D'Agata, Denise Colombo, Stefano Felici, Valeria Gretter, Susanna Facchetti, Gaia Pecorelli, Cristina Quecchia PD34 Sensitisation to an inert aeroallergen in weaning rats and longstanding disease, in a sensitisation-tolerant and easily tolerisable rodent strain George Guibas, Evangelia Spandou, Spyridon Megremis, Peter West, Nikolaos Papadopoulos PD35 Bacterial and fungi exposure in school and allergic sensitisation in children João Cavaleiro Rufo, Joana Madureira, Inês Paciência, Lívia Aguiar, Patrícia Padrão, Mariana Pinto, Luís Delgado, Pedro Moreira, João Paulo Teixeira, Eduardo Oliveira Fernandes, André Moreira PD36 Comparative study of allergy rhinitis between two populations: children vs. adults Adriana Izquierdo Dominguez, Antonio Valero, Joaquim Mullol, Alfonso Del Cuvillo, Javier Montoro, Ignacio Jauregui, Joan Bartra, Ignacio Davila, Marta Ferrer, Joaquin Sastre POSTER VIEWING SESSION 1: Inflammation—Genetics—Immunology—Dermatology (PP01–PP09) PP01 Immune profile in late pregnancy: immunological markers in atopic asthmaticwomen as risk factors for atopy in the progeny Catarina Martins, Jorge Lima, Maria José Leandro, Glória Nunes, Jorge Cunha Branco, Hélder Trindade, Luis Miguel Borrego PP02 The impact of neonatal sepsis on development of allergic diseases Secil Conkar, Mehtap Kilic, Canan Aygun, Recep Sancak PP03 Clinical overview of selective IgE deficiency in childhood Athina Papadopoulou, Eleni Tagalaki, Lambros Banos, Anna Vlachou, Fotini Giannoula, Despina Mermiri PP04 Inverse relationship between serum 25(ΟΗ) vitamin D3 and total IgE in children and adolescence Athina Papadopoulou, Stavroula Lampidi, Marina Pavlakou, Maria Kryoni, Kostas Makris PP05 PP06 PP07 Asthma control questionnaire and specific IgE in children Snezhina Lazova, Guergana Petrova, Dimitrinka Miteva, Penka Perenovska PP08 Features of chronic urticaria of adolescents Aliya Klyucharova, Olesya Skorohodkina PP09 Cutaneous mastocytosis in children: a clinical analysis of 8 cases in Greece Dimitra Koumaki, Alkisti Manousaki, Maria Agrapidi, Lida Iatridou, Omima Eruk, Konstantinos Myridakis, Emmanouil Manousakis, Vasiliki Koumaki POSTER VIEWING SESSION 2: Food allergy—Anaphylaxis (PP10–PP47) PP10 Prognostic factors in egg allergy Maria Dimou, Maria Ingemansson, Gunilla Hedlin PP11 Evaluation of the efficacy of an amino acid-based formula in infants who are intolerant to extensively hydrolysed protein formula Nitida Pastor, Delphine de Boissieu, Jon Vanderhoof, Nancy Moore, Kaitlin Maditz PP12 Anaphylaxis and epinephrine auto-injector use: a survey of pediatric trainees Adeli Mehdi, Shaza Elhassan, Carolin Beck, Ahmed Al-Hammadi PP13 Anaphylaxis in children: acute management in the Emergency Department Ioana Maris, Ronan O'Sullivan, Jonathan Hourihane, PP14 Understanding Cumbrian schools preparedness in managing children at risk of anaphylaxis in order to provide training and support which will create healthy and safe environments for children with allergies George Raptis, Louise Michaelis PP15 A new valid and reliable parent and child questionnaire to measure the impact of food protein enterocolitis syndrome on children: the FPIES Quality of Life Questionnaire (FPIESQL), Parent and Child Short Form Audrey DunnGalvin, Matthew Greenhawt, Carina Venter, Jonathan Hourihane PP16 An in-depth case study investigation of the experiences of teenagers and young adults in growing up and living with food allergy with emphasis on coping, management and risk, support, and social and self-identity Evelyn O'Regan, Duncan Cronin, Jonathan Hourihane, Anna O'Reilly, Audrey DunnGalvin PP17 Cow's milk protein allergy in Constantine. A retrospective study of 62 cases between 1996 and 2013 Foued Abdelaziz, Dounia Khelifi-Touhami, Nihad Selim, Tahar Khelifi-Touhami PP18 PP19 Cow's milk and egg oral immunotherapy in children older than 5 years Pablo Merida, Ana Mª Plaza, Juan Heber Castellanos, Adrianna Machinena, Montserrat Alvaro Lozano, Jaime Lozano, Olga Dominguez, Monica Piquer, Rosa Jimenez, Mª Teresa Giner PP20 Professionals' awareness of management of Cow's Milk Protein Allergy (CMPA) in North Wales Hospitals Konstantinos Kakleas, Manohar Joishy, Wendmu Maskele, Huw R. Jenkins PP21 PP22 Anaphylaxis: the great unknown for teachers. Presentation of a protocol for schools Mercedes Escarrer, Agustín Madroñero, Maria Teresa Guerra, Juan Carlos Julia, Juan Carlos Cerda, Javier Contreras, Eulalia Tauler, Maria Jesus Vidorreta, Ana Rojo, Silvia Del Valle PP23 Challenges facing children with food allergies and their parents in out of school activity sectors Niamh Flynn PP24 A review of food challenges at a Regional Irish Centre Gary Foley, Carol Harmon, John Fitzsimons PP25 The use of epinephrine in infants with anaphylaxis Krasimira Baynova, Ávila Maria Del Robledo, Labella Marina PP26 PP27 PP28 Mother's psychological state predicts the expression of symptoms in food allergic children Aaron Cortes, Alicia Sciaraffia, Angela Castillo PP29 The correlation between sIgE towards tree nuts and birch pollen in a Danish Pediatric Allergy Clinic Nanna Juel-Berg, Kirsten Skamstrup Hansen, Lars Kærgaard Poulsen PP30 Food allergy in children: evaluation of parents' use of online social media Andreia Florina Nita, Ioana Valentina Nenciu, Adina Lazar, Dumitru Oraseanu PP31 The impact of food allergy on quality of life: FAQLQ questionnaire Rita Aguiar, Anabela Lopes, Maria J. Paes, Amélia S. Santos, M. A. Pereira-Barbosa PP32 An unexpected cause of anaphylaxis: potato Hatice Eke Gungor, Salih Uytun, Umit Murat Sahiner, Yasemin Altuner Torun PP33 Is it clinical phenotype of allergic diseases determined by sensitisation to food? Mirjana Zivanovic, Marina Atanasković-Marković PP34 PP35 Prescribing adrenaline auto-injectors in children in 2014: the data from regional pediatricians Tina Vesel, Mihaela Nahtigal, Andreja Obermayer-Temlin, Eva Šoster Križnik, Mirjana Maslar, Ruben Bizjak, Marjeta Tomšič-Matic, Sonja Posega-Devetak, Maja Skerbinjek-Kavalar, Mateja Predalič, Tadej Avčin PP36 Who should have an adrenaline autoinjector? Adherence to the European and French guidelines among 121 allergists from the Allergy Vigilance Network Guillaume Pouessel, Etienne Beaudouin, Anne M. Moneret-Vautrin, Antoine Deschildre, Allergy Vigilance Network PP37 Anaphylaxis by Anacardium Occidentale Marta Viñas, Bartolomé Borja, Nora Hernández, Mª José Castillo, Adriana Izquierdo, Marcel Ibero PP38 Anaphylaxis with honey in a child S. Tolga Yavuz, Ali Gungor, Betul Buyuktiryaki, Ozan Koc, Can Naci Kocabas, Faysal Gok PP39 Evaluation of courses adopted to children on prevention, recognition and management of anaphylaxis Tina Vesel, Mihaela Nahtigal PP40 Symptomatic dust mites and shrimp allergy: three pediatric case reports Filipa Almeida, Susana Lopes, Cristina Madureira, Tânia Lopes, Fernanda Carvalho PP41 Poor identification rates of nuts by high risk individuals: a call for improved education and support for families Camille Heming, Emily Garrett, Adam Blackstock, Santanu Maity, Rahul Chodhari PP42 DAFALL: database of food allergies in the Czech Republic Simona Belohlavkova, Eliska Kopelentova, Petr Visek, Ivana Setinova, Ivana Svarcova PP43 Serological cross-reactivity between grass and wheat is not only caused by profilins and CCDs Sigrid Sjölander, Nora Nilsson, Malin Berthold, Helena Ekoff, Gunilla Hedlin, Magnus Borres, Caroline Nilsson PP44 Oil body associated proteins in children with nuts allergy. Allergens to consider in IgE-mediated nuts allergy Loreto González Domínguez, Cristina Muñoz Archidona, Ana Moreira Jorge, Sergio Quevedo Teruel, Teresa Bracamonte Bermejo, Miriam Castillo Fernández, Fernando Pineda de la Losa, Luis Ángel Echeverría Zudaire PP45 PP46 Protective effect of helicobacter pylori infection against food allergy in children Olga Vrani, Antigone Mavroudi, Maria Fotoulaki, Maria Emporiadou, Kleomenis Spiroglou, Ioannis Xinias PP47 Anaphylaxis pathway: A road tryp-tase to success? Helyeh A. Sadreddini, Mia Warnes, Donna Traves POSTER VIEWING SESSION 3: Miscellaneous (PP48–PP58) PP48 Surveillance study on safety of SLIT in pediatric population Ivana Djuric-Filipovic, Zorica Zivkovic, Snežana Zivanovic, Gordana Kostić, Đorđe Filipovic PP49 Efficacy and safety of mixed mite subcutaneous immunotherapy among allergic rhinitis patients in the Northeastern Thailand Sawapon Sittisomwong, Siripong Sittisomwong PP50 Effect of inhaled beclomethasone or placebo on brain stem activity in a patient chronically treated with steroids: preliminary report Zygmunt Podolec, Marcin Hartel, Daria Panek, Magdalena Podolec-Rubiś, Tomasz Banasik PP51 Sensitisation to aeroallergens in patients with allergic rhinitis, asthma and atopic dermatitis in Shiraz, Southwestern Iran Elham Abbasi, Mozhgan Moghtaderi PP52 Referring a child for allergy test: how appropriate are we? Phani Sanneerappa, Alina Deliu, Moosa Kutty, Nagabathula Ramesh PP53 EBV lymphoproliferative disease and cardiac lymphoma in a STK4 deficient patient Roya Sherkat, Mohammad Reza Sabri, Bahar Dehghan, Hamid Bigdelian, Nahid Raeesi, Mino Afshar, Hamid Rahimi, Christoph Klein PP54 A case study: the effect of massive honeybees attack on various body parameters atopic girl including allergy Mohemid Al-Jebouri PP55 The role of TLR9, NLRP3 and proIL-1β in activation of antiviral innate immunity Oxana A. Svitich, Daria O. Zubacheva, Dmitrii A. Potemkin, Ludmila V. Gankovskaya, Vitalii V. Zverev PP56 Overnight pulse oximetry, as a screening tool to diagnose obstructive sleep apnoea. How effective is it? Phani Sanneerappa, Elaine OB Doyle, Paul Gallagher, Nagabathula Ramesh PP57 The presentation and management of acute urticaria and allergic reactions in children in a multi-ethnic, inner city Emergency Department (ED) Sherine Dewlett, Kin Man, Minal Gandhi, James Pocock, Anna Gerrardhughes PP58 Food allergens responsible for delayed-type sensitisation in atopy patch test in children diagnosed with autism spectrum disorder Jolanta Wasilewska, Maciej Kaczmarski, Dariusz Lebensztejn POSTER VIEWING SESSION 4: Asthma—Rhinitis (PP59–PP87) PP59 Systematic review of incense as a trigger factor for asthma Chandramani Thuraisingham, Davendralingam Sinniah PP60 Increased risks of mood and anxiety disorders in children with asthma Yue Chen, Xiaomei Mei PP61 PP62 Asthma Control Test (ACT) and Pediatric Asthma Quality of Life Questionnaire (PAQLQ) association in children Sebnem Ozdogan, Pinar Karadeniz, Durdugul Ayyildiz-Emecen, Ummuhan Oncul PP63 Seasonal and gender variations in vitamin D levels in children with asthma and its association with pulmonary function tests Sebnem Ozdogan, Gizem Sari, Sabanur Cavdar PP64 Defining treatment response in childhood asthma: rationale and design of the Pharmacogenomics in the Childhood Asthma (PiCA) consortium Niloufar Farzan, Susanne J. Vijverberg, Colin J. Palmer, Kelan G. Tantisira, Anke-Hilseon Maitland-van der Zee behalf of the PiCA consortium PP65 Prevalence of asthma and allergic disease in patients with inflammatory disease compared to celiac disease Fatma Yavuzyilmaz, Sebnem Ozdogan, Nafiye Urganci, Merve Usta PP66 A severe case with cystic fibrosis (CF) asthma Mehmet Hoxha, Maksim Basho PP67 Severe asthma exacerbation complicated with pneumothorax in a child with uncontrolled asthma due to poor treatment compliance Ioana Valentina Nenciu, Andreia Florina Nita, Adina Lazar, Alexandru Ulmeanu, Carmen Zapucioiu, Dumitru Oraseanu PP68 Evaluation of the Pediatric Quality of Life inventory (PedsQL) asthma module among low income asthmatic children and adolescents in Sao Paolo, Brazil Gustavo F. Wandalsen, Fernanda Monteiro, Dirceu Solé PP69 Early initiation of specific immunotherapy in asthma patients leads to higher benefits Blerta Lame, Eris Mesonjesi, Arjeta Sherri PP70 Treatment resistant asthma and rhinosinusitis with recurrent pulmonary infections. Is it primary ciliary dyskinesia? Alkerta Ibranji, Laert Gjati, Gjustina Loloci, Ardii Bardhi PP71 The comparison of sensitisation to animal allergens in children- and adult- onset patients with asthma Behnam Moghtaderi, Shirin Farjadian, Dorna Eghtedari PP72 Characterisation of children less than five years with wheezing episodes in Cali, Colombia Manuela Olaya, Laura Del Mar Vasquez, Luis Fernando Ramirez, Carlos Daniel Serrano PP73 Evaluation of the patients with recurrent croup Belgin Usta Guc, Suna Asilsoy, Fulya Ozer PP74 Obesity in adolescence compromising the asthma control Guergana Petrova, Sylvia Shopova, Vera Papochieva, Snezhina Lazova, Dimitrinka Miteva, Penka Perenovska PP75 Sleep behavior in children with persistent allergic rhinitis Gustavo F. Wandalsen, Jessica Loekmanwidjaja, Márcia Mallozi, Dirceu Solé PP76 Randomised trial of the safety of MP29-02* compared with fluticasone propionate nasal spray in children aged ≥4 years to <12 years with allergic rhinitis William Berger, Ulrich Wahn, Paul Ratner, Daniel Soteres PP77 Safety and tolerability evaluation of bilastine 10 mg in children from 2 to 11 years of age with allergic rhinoconjunctivitis or urticaria Zoltán Novák, Anahí Yáñez, Kiss Ildikó, Piotr Kuna, Miguel Tortajada, Román Valiente, the Bilastine Pediatric Safety Study Group PP78 Sensitisation to Alternaria alternata: Is it a risk factor for severe rhinitis? Susana Lopes, Filipa Almeida, Tânia Lopes, Cristina Madureira, José Oliveira, Fernanda Carvalho PP79 Validation of the Patient Benefit Index (PBI) for the assessment of patient-related outcomes in allergic rhinitis in children Julia Feuerhahn, Christine Blome, Meike Hadler, Efstrathios Karagiannis, Anna Langenbruch, Matthias Augustin PP80 Efficacy of sublingual tablet of house dust mite allergen extracts in adolescents with house dust mite-associated allergic rhinitis Michel Roux, Shinji Kakudo, Efstrathios Karagiannis, Robert K. Zeldin PP81 Lung function improvement in a child treated with omalizumab for bronchial asthma Anna Sokolova, Tiago Milheiro Silva PP82 How to treat a child suffering from asthma, allergic rhinitis, allergy to peanuts and diabetes at the same time? Snezana S. Zivanovic, Vesna Cvetkovic, Ivana Nikolic, Sonja J. Zivanovic PP83 Nitric oxide in exhaled air in the relationship of the degree of sensitisation to aeroallergens Snezana S. Zivanovic, Ljiljana Saranac, Ivana Nikolic, Sonja J. Zivanovic, Zorica Zivkovic PP84 Clinical basis of diagnostic errors in pediatric asthma Zoia Nesterenko PP85 PP86 Childhood asthma control in Serbia and organised Asthma Educational Intervention (AEI) Snezana Radic, Branislava Milenkovic, Spomenka Smiljanic, Milka Micic-Stanijevic, Olivera Calovic PP87 Experience from a group of adolescents with severe allergic asthma treated with Omalizumab Anne Marie Bro Hofbauer, Lone Agertoft THEMATIC POSTER SESSION 1: Prevention and Treatment—Epidemiology (TP01–TP18) TP01 A cost effective primary school asthma education program: pilot study from inner London schools Lucy Everson, Jessica Kearney, Jonny Coppel, Simon Braithwaite, Rahul Chodhari TP02 The prevalence of allergic diseases among 14–15 years old adolescents in two Danish birth cohorts 14 years apart Elisabeth S. Christiansen, Henrik Fomsgaard Kjaer, Esben Eller, Charlotte G. Mørtz, Susanne Halken TP03 Does pattern of sensitisation to phleum pratense change with age? Is it different in children with allergic rhinitis or asthma? Cristina Román India, Ana Moreira Jorge, Loreto González Domínguez, Cristina Muñoz Archidona, Sergio Quevedo Teruel, Teresa Bracamonte Bermejo, Juana Jiménez Jiménez, Luis Echeverría Zudaire TP04 Practicalities of prevention of peanut allergy: modelling a national response to LEAP Cathal O'Connor, Jonathan Hourihane TP05 Comparison of the influence of sunflower seed oil and skin care lotion on the skin barrier function of newborns: a randomised controlled trial Varvara Kanti, Lena Lünnemann, Günther Malise, Laine Ludriksone, Andrea Stroux, Wolfgang Henrich, Michael Abu-Dakn, Ulrike Blume-Peytavi, Natalie Garcia Bartels TP06 The effect of daily skin care on skin barrier properties in infants with dry skin and risk for atopic dermatitis Varvara Kanti, Lena Lünnemann, Laine Ludriksone, Marianne Schario, Andrea Stroux, Ulrike Blume-Peytavi, Natalie Garcia Bartels TP07 Change in sum total aeroallergen skin prick test wheal diameters at 6 months predicts which children will respond to subcutaneous immunotherapy by three years Thorsten Stanley, Nicolien Brandenbarg TP08 Are mobile apps regarding adrenaline auto-injectors accessed by adolescents for support and education in the community? Alia Boardman, Gary McGreevy, Emily Rodger, Katherine Knight, Victoria Timms, Trisha Taylor, Gemma Scanlan, Roisin Fitzsimons TP09 TP10 Prevention of early atopic dermatitis among low-atopy-risk infants by immunoactive prebiotics is not sustained after the first year of life Grüber Christoph, Ulrich Wahn, Margriet van Stuivenberg, Fabio Mosca, Guido Moro, Gaetano Chirico, Christian P. Braegger, Joseph Riedler, Yalcin Yavuz, Günther Boehm TP11 TP12 TP13 Treatment with Omalizumab in a 16-year-old Caucasian girl with refractory solar urticaria Stefania Arasi, Giuseppe Crisafulli, Lucia Caminiti, Federica Porcaro, Giovanni Battista Pajno TP14 Ultra-pure soft water ameliorates skin conditions of adult and child patients with atopic dermatitis Akane Tanaka, Yaei Togawa, Kumiko Oida, Naotomo Kambe, Peter Arkwright, Yosuke Amagai, Naoki Shimojo, Yasunori Sato, Hiroyuki Mochizuki, Hyosun Jang, Saori Ishizaka, Hiroshi Matsuda TP15 Potential adjuvant effect of immunomodulator to improve specific immunotherapy in asthmatic child Wisnu Barlianto, Ery Olivianto, H. M. S. Chandra Kusuma TP16 How can Component Resolved Diagnosis (CRD) influence in Specific Immunotherapy (SIT) prescription, in a Spanish children population Ana Moreira Jorge, Cristina Román India, Loreto González Domínguez, Cristina Muñoz Archidona, Juana Jiménez Jiménez, Teresa Bracamonte Bermejo, Sergio Quevedo Teruel, Luis Echeverría Zudaire TP17 Mitochondrial dysfunction in food allergy: effects ofL. rhamnosus GG in a mice model of peanut allergy Rosita Aitoro, Mariapia Mollica, Roberto Berni Canani, Giovanna Trinchese, Elena Alfano, Antonio Amoroso, Lorella Paparo, Francesco Amato, Claudio Pirozzi, Antonio Calignano, Rosaria Meli TP18 Prediction of atopic diseases in childhood: elevated blood eosinophils in infancy in a high risk birth cohort Siri Rossberg, Kerstin Gerhold, Kurt Zimmermann, Mohammad Zaino, Thomas Geske, Eckard Hamelmann, Susanne Lau THEMATIC POSTER SESSION 2: Food allergy—Anaphylaxis (TP19–TP38) TP19 TP20 TP21 Double-blind provocation tests in non-IgE mediated cow's milk allergy and the occurrence of placebo reactions Sarah Bogovic, Jochem van den Berg, Chantal Janssen TP22 Gradual introduction of baked egg (BE) in egg allergic patients under 2 years old Angela Claver TP23 Randomised controlled trial of SOTI with raw hen's egg in children with persistent egg allergy I: safety and efficacy of daily vs. weekly protocols of induction Mª Flor Martin-Muñoz, C. Martorell, M. T. Belver, E. Alonso Lebrero, L. Zapatero, V. Fuentes, M. Piqué, A. Plaza, C. Muñoz, A. Martorell, Cristina Blasco, B. Villa, C. Gómez, S. Nevot, J. M. García, L. Echeverria TP24 Randomised controlled trial of SOTI with raw hen's egg in children with persistent egg allergy II: a randomised controlled trial to study a safer, more effective and easy to perform maintenance (daily vs. every two days) pattern of egg SOTI Mª Flor Martin-Muñoz, C. Martorell, M. T. Belver, E. Alonso Lebrero, L. Zapatero, V. Fuentes, M. Piqué, A. Plaza, C. Muñoz, A. Martorell, Cristina Blasco, B. Villa, C. Gómez, S. Nevot, J. M. García, L. Echeverria TP25 Determining the safety of baked egg home reintroduction for children with mild egg allergy Brenda DeWitt, Judith Holloway, Donald Hodge TP26 Demographics, investigations and patterns of sensitisation in children with oral allergy syndrome in a London Teaching Hospital Sian Ludman, Merhdad Jafari-Mamaghani, Rosemary Ebling, Adam T. Fox, Gideon Lack, George Du Toit TP27 Airborne peanut challenge in children: allergic reactions are rare Sofia Lovén Björkman, Caroline Nilsson, Natalia Ballardini TP28 The nutty question on Pediatric Wards: to be or "nut" to be? Supriyo Basu, Jenny Hallet, Jyothi Srinivas TP29 TP30 TP31 Allergy education in nursery schools Hazel Stringer, Nicola Jay TP32 Food allergy in the first year of life Tânia Lopes, Cristina Madureira, Filipa Almeida, Susana Lopes, Paula Fonseca, Clara Vieira, Fernanda Carvalho TP33 Prevalence and geographic distribution of oral allergy syndrome in Italian children: a multicenter study Carla Mastrorilli, Carlo Caffarelli, Riccardo Asero, Salvatore Tripodi, Arianna Dondi, Gianpaolo Ricci, Carlotta Povesi Dascola, Elisabetta Calamelli, Francesca Cipriani, Andrea Di Rienzo Businco, Annamaria Bianchi, Paolo Candelotti, Tullio Frediani, Carmen Verga, Paolo Maria Matricardi TP34 Are common standardised allergen extracts used in skin test enough in the diagnosis of nuts allergy? Cristina Muñoz Archidona, Loreto González Domínguez, Ana Moreira Jorge, Sergio Quevedo Teruel, Teresa Bracamonte Bermejo, Miriam Castillo Fernández, Fernando Pineda de la Losa, Luis Ángel Echeverría Zudaire TP35 Evaluation of IgE sensitisation in children with allergic proctocolitis and its relationship to atopic dermatitis Despina Mermiri, Paraskevi Korovessi, Skevi Tiliakou, Evaggelia Tavoulari, Kalliopi-Maria Moraiti, Fotini Giannoula, Athina Papadopoulou TP36 Food allergy in children: are we managing them appropriately in the Emergency Department? Wan Jean Tee, Samir Deiratany, Raymond Seedhoo, Roisin McNamara, Ike Okafor TP37 Importance of oil body associated allergenic proteins in nuts suspected allergy children Loreto González Domínguez, Ana Moreira Jorge, Cristina Muñoz Archidona, Teresa Bracamonte Bermejo, Sergio Quevedo Teruel, Fernando Pineda de la Losa, Miriam Castillo Fernández, Luis Ángel Echeverría Zudaire TP38 Practical application of basophil activation test in children with food allergy Ekaterina Khaleva, Gennady Novic, Natalia Bychkova THEMATIC POSTER SESSION 3: Asthma (TP39–TP57) TP39 Effect of corticosteroid therapy upon serum magnesium level in chronic asthmatic children Amany Abd Al-Aziz, Amany Fatouh, Ayat Motawie, Eman El Bostany, Amr Ibrahim TP40 ADAM33 in Bulgarian children with asthma Guergana Petrova, Dimitrinka Miteva, Snezhina Lazova, Penka Perenovska, Sylvia Andonova, Alexey Savov TP41 TP42 The impact of vitamin D serum levels in asthma and allergic rhinitis Maria Zoto, Marialena Kyriakakou, Paraskevi Xepapadaki, Nikolaos G. Papadopoulos TP43 Life-threatening, first reported, paradoxical bronchospasm after nebulised Salbutamol in a 10 year old child Paraskevi Korovessi, Mariza Vassilopoulou, Athina Balaska, Lambros Banos, Stavroula Kostaridou, Despina Mermiri TP44 TP45 Asthma symptoms in children with treatment for allergic rhinoconjunctivitis Jorien Wartna, Arthur M. Bohnen, Gijs Elshout, David H. J. Pols, Patrick J. E. Bindels Erasmus MC, Rotterdam, The Netherlands TP46 Atopy increased the risk of developing exercise-induced bronchoconstriction in young athletes Sven F. Seys; Ellen Dilissen, Sarah Van der Eycken, An-Sofie Schelpe, Gudrun Marijsse, Thierry Troosters, Vincent Vanbelle, Sven Aertgeerts, Jan L. Ceuppens, Lieven J. Dupont, Koen Peers, Dominique M. Bullens TP47 The effect of higher BMI on risk for asthma and treatment outcome in overweight and obese children Ivana Banic, Sandra Bulat Lokas, Jelena Zivkovic, Boro Nogalo, Iva Mrkic Kobal, Davor Plavec, Mirjana Turkalj TP48 TP49 TP50 TP51 TP52 The impact of a multidisciplinary project intended to change the culture of nebulisers towards pressurised metered dose inhalers Georgeta Oliveira, Katharine Pike, Alda Melo, Tomás Amélia, José Carlos Cidrais Rodrigues, Cristina Serrano, José Manuel Lopes dos Santos, Carla Lopes TP53 TP54 TP55 TP56 Increased asthma control in patients with severe persistent allergic asthma after 12 month of nightly temperature controlled laminar airflow (TLA) Eckard Hamelmann, Uwe Schauer, Karl-Christian Bergmann TP57 THEMATIC POSTER SESSION 4: Drug allergy—Dermatology (TP58–TP77) TP58 Should we proceed directly to provocation challenges to diagnose drug allergy? Our experience says yes Luis Moral, Teresa Toral, Nuria Marco, Beléns García Avilés, Mª Jesús Fuentes, Jesús Garde, Cristina Montahud, Javier Perona, Mª José Forniés TP59 Anaphylaxis to 13-valent pneumococcal vaccine Esozia Arroabarren, Marta Anda, Maria Luisa Sanz, Maria Teresa Lizaso, Candida Arregui TP60 Intrapartum antibiotic exposure for treatment of group B streptococcus was not associated with the development of penicillin allergy in children Sara May, Martha Hartz, Avni Joshi, Miguel A. Park TP61 Evaluation of suspected drug hypersensitivity reactions in 169 children referred to the General Hospital Sonja Posega Devetak, Tina Vesel, Anja Koren Jeverica, Tadej Avčin TP62 Drug provocation testing: experience of a tertiary hospital Leonor Castro, Carolina Gouveia, Ana Carvalho Marques, Antonio Jorge Cabral TP63 Perioperative anaphylaxis: a growing concern in pediatric population Luis Amaral, Fabrícia Carolino, Eunice Castro, Madalena Passos, Josefina R. Cernadas TP64 Raising awareness of hypersensitivity to non-steroidal anti-inflammatory drugs in the pediatric age Fabrícia Carolino, Luís Amaral, Eunice Dias de Castro, Josefina R. Cernadas TP65 Perioperative anaphylaxis in young children: how to confirm the suspicion Josefina R. Cernadas, Fabrícia Carolino, Luís Amaral, Fernando Pineda, Armanda Gomes TP66 A case study of a child suspected to be penicillin allergic-digging deeper Katherine Knight, Roisin Fitzsimons, Helen Brough TP67 Prevalence, characteristics and risk factors of hypersensitivity reactions to antibiotics in patients with cystic fibrosis Jobst Röhmel, Carsten Schwarz, Anne Mehl, Philippe Stock, Doris Staab TP68 Antibiotic drug hypersensitivity in cystic fibrosis: A pilot study using cellular allergy tests for diagnostics Jobst Röhmel, Carsten Schwarz, Christine Seib, Doris Staab, Philippe Stock TP69 Oral antibiotics challenges in children Anita Critchlow, Alyson Barber, Nicola Jay TP70 Hypersensitivity reaction to vancomycin: a new successful desensitization protocol Belen Delavalle, Teresa Garriga, Blanca Vilá, Cristina Blasco TP71 TP72 Clinical phenotypes according to FLG gene loss of function mutations in children with atopic dermatitis Francesca Cipriani, Annalisa Astolfi, Costanza Di Chiara, Elisabetta Calamelli, Iria Neri, Annalisa Patrizi, Gianpaolo Ricci TP73 TP74 Urticaria in children: clinical and epidemiological features Katerina Neskorodova, Asya Kudryavtseva TP75 TP76 Acute urticaria at the Pediatrics Emergency Department: is it allergy? Esozia Arroabarren, Jorge Alvarez, Marta Anda, Miriam Palacios, Marta Martinez-Merino, Ibone Vaquero TP77